Antioxidant activities of postbiotics produced by several Lactobacillus plantarum strains using reconstituted media - Merzza, Humam A.; Idris, Alshelmani M.; Chwen, Loh, T.; Ling, Foo, H. (Scientific Journal of University of Benghazi, 2021)
The current study was conducted to determine the antioxidant activity of postbiotics produced by various strains of Lactobacillus plantarum grown in reconstituted media, as well as to identify the one with the best antioxidant activity based on scavenging free radicals. By using reconstituted media, six strains of L. plantarum (RG11, RG14, RI11, UL4, TL1, and RS5) were used to produce the postbiotics. The antioxidant activity of the postbiotics was determined using the 2,2-Diphenyl-1-Picryl-hydrazyl (DPPH) assay and 2,2’-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) assays. A significantly higher antioxidant activity of postbiotics was observed in RI11 compared to other postbiotics, whereas UL4 and RS5 were significantly higher (P<0.05) compared with RG11, RG14, and TL1. However, no significant difference was recorded between RG11, RG14, and TL1 in the postbiotics scavenging activity. Both the DPPH assay and ABTS radical cation scavenging potential showed that the various strains possess antioxidant activity.